2018
DOI: 10.20945/2359-3997000000021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metabolic surgery on type 1 diabetes: meta-analysis

Abstract: Objective: Metabolic and bariatric surgery has a definite role in the management of obese patients with type 2 diabetes mellitus (T2DM). There is also evidence of such surgery improving the health of type 1 diabetic (T1DM) patients. The aim of this paper is to explore the effect of metabolic and bariatric surgery on T1DM. Materials and methods: A comprehensive search of PubMed and Google Scholar was performed to identify relevant papers reporting metabolic and bariatric surgery effects on T1DM. A statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…However, there is preliminary evidence that in select individuals with type 1 diabetes and excess adiposity, newer pharmacotherapy (i.e., glucagonlike peptide 1 receptor agonists or sodium-glucose cotransporter 2 inhibitors) (195,196) can decrease body weight and improve glycemia, though they are currently not indicated. In addition, metabolic surgery in appropriate candidates can decrease body weight and improve glycemia (197,198).…”
Section: Energy Balance and Weight Managementmentioning
confidence: 99%
“…However, there is preliminary evidence that in select individuals with type 1 diabetes and excess adiposity, newer pharmacotherapy (i.e., glucagonlike peptide 1 receptor agonists or sodium-glucose cotransporter 2 inhibitors) (195,196) can decrease body weight and improve glycemia, though they are currently not indicated. In addition, metabolic surgery in appropriate candidates can decrease body weight and improve glycemia (197,198).…”
Section: Energy Balance and Weight Managementmentioning
confidence: 99%
“…There are limited data on the effects of bariatric or metabolic procedures on T1D. In a 2018 meta‐analysis by Hussain , only 9 studies (N = 78 patients) demonstrated improvements in A1C, insulin dosing, and BMI. Improvements in diabetes management were not exclusively related to excess weight loss, arguing for roles of other factors.…”
Section: Executive Summarymentioning
confidence: 99%
“…A recent meta‐analysis of nine studies that included 78 obese people with type 1 diabetes undergoing metabolic and bariatric surgery showed a significant reduction in insulin dose ( P =0.0001) and BMI ( P =0.00001), but no significant improvement in HbA 1c .…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%